Factors which affect the application and implementation of a spinal motion restriction protocol by prehospital providers in low resource settings: a scoping review - Geduld, Charlene (Division of Emergency Medicine, 2022)
The South African Professional Board for Emergency Care prehospital Clinical Practice Guideline (CPG) recommends that emergency medical services (EMS) make use of the National Emergency X Radiography Utilization Study (NEXUS) rule and Canadian C-spine Rule (CCSR) when managing traumatic spinal injury. However, the safety and effectiveness of prehospital clinical spinal clearance or spinal motion restriction (SMR) decision support tools within poorly resourced settings are unclear. We conducted a scoping review on clinical spinal clearance and selective SMR decision support tools which aimed at identifying possible barriers to their implementation, safety, and effectiveness when used by EMS personnel. Studies were included if they described the use of clinical spinal clearance or SMR decision tools in first line management of blunt trauma patients by medical practitioners in the Emergency Department (ED) or by EMS personnel working in a prehospital setting. After screening, 42 documents fulfilled the inclusion criteria. Several selective SMR decision support tools have been implemented in the prehospital setting, the most common of which were those based on the NEXUS and the CCSR tools. Only one study evaluated the safety and efficacy of the NEXUS rule when used by EMS personnel. The limited prehospital literature available investigating either the NEXUS rule or CCSR therefore makes it difficult to determine its appropriateness for adoption and implementation by EMS personnel in other prehospital settings such as that of South Africa. Furthermore, commonly found prehospital NEXUS-based decision tools presented with unique challenges related to the subjective nature of some of the individual components of the decision tool. This leaves the decision tool open to interpretation by examiners and is especially relevant in settings, such as South Africa, where there are many different levels in scope of practices. This increases the risk of the patient being either under-triaged or over-triaged. More studies are therefore needed to definitively assess for the safety, efficacy and effectiveness of clinical spine clearance within the prehospital setting. It is believed that a selective SMR decision tool which has more specific instructions for the prehospital practitioner may be able to accommodate such challenges and is an area which needs further investigation.